ОЦЕНКА ФОРМИРОВАНИЯ КОМПЕТЕНЦИЙ У АСПИРАНТОВ ВТОРОГО ГОДА ОБУЧЕНИЯ - Ваулин, Георгий Фёдорович; Тихомирова, Александра Александровна; Дохов, Михаил Александрович; Котиков, Павел Евгеньевич (Медицина: теория и практика, 2020)